A higher-order difference scheme of the Cabaret class for solving the transport equation - Solovjev, A.V.; Danilin, A.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2018)
A new difference scheme of the Cabaret class with a higher order of accuracy for solving the scalar transport equation is proposed. The order of approximation of this difference scheme is equal to four. The balance-characteristic representation of the scheme is constructed and the dispersion properties are given. For the proposed difference scheme, a number of examples to solve the transport equation for smooth and discontinuous profiles are considered in comparison with the classical Cabaret scheme.